Does the implementation of clinical pathways affect hierarchical structures within a surgical department?: A qualitative study - Ronellenfitsch, Ulrich; Loerbroks, Adrian; Schwarzbach, Matthias (International surgery, 2018)
Objective: To explore effects of the implementation of clinical pathways (CPs) on hierarchical structures within a surgical department. Summary of background data: CPs are care plans stipulating diagnostic and therapeutic measures along a time axis for a given condition or procedure. They are widely used in surgery. There is limited evidence to what extent CP implementation has an effect on hierarchical structures within surgical departments. Methods: Semistructured individual interviews were conducted with key members of a CP project team in a large academic surgery department. Interviews were carried out by an external researcher to increase the likelihood of obtaining unbiased opinions. Using an interview guide, it was ensured that respondents provided opinions on various issues related to CP implementation, including hierarchical relationships within the department, but also between caregivers and patients. The transcribed text was independently content analyzed by 2 researchers who converged their findings. Results: Clinical pathway implementation changed perceived surgical hierarchy from a top-down to a participatory approach. However, it was acknowledged that some form of hierarchy is required to ensure successful clinical pathway implementation. Respondents felt that clinical pathways changed surgical culture from a largely eminence-based to more evidence-based medicine. Conclusions: The implementation of CPs potentially affects several dimensions of surgical hierarchy. It changes “traditional” surgical hierarchy and is associated with perception of increased autonomy and competency in junior staff. The clinical approach appears to shift from eminence- to evidence-based medicine. The knowledge about these changes is important for carrying out CP projects in surgery.